A BOOK REVIEW: A GOOD START, THOUGH INCOMPLETE, FOR CREATIVE WRITERS - Iwan Sulistiawan (Celt: A Journal of Culture, English Language Teaching & Literature, 2012)
Carol Whiteley tries to guide the readers through the entire process of creative writing, from writing preparation and getting the ideas to drafting and editing what has been written. Whiteley also expects readers to learn all about the different formats of creative writing and find hundreds of writing tips, resources, examples, inspirational excerpts, advice and encouragement.